Infographics and Mathematics: A Mechanism for Effective Learning in the Classroom. Issue 2 (7th February 2016) - Sudakov, Ivan; Bellsky, Thomas; Usenyuk, Svetlana; Polyakova, Victoria V.
Abstract: This work discusses the creation and use of infographics in an undergraduate mathematics course. Infographics are a visualization of information that combines data, formulas, and images. This article discusses how to form an infographic and uses infographics on topics within mathematics and climate as examples. It concludes with survey data from undergraduate students on both the general use of infographics and on the specific infographics designed by the authors.